Catch It If You Can: Copper-Catalyzed (Transfer) Hydrogenation Reactions and Coupling Reactions by Intercepting Reactive Intermediates Thereof - Brechmann, Lea T.; Teichert, Johannes F. (Synthesis, 2020)
The key reactive intermediate of copper(I)-catalyzed alkyne semihydrogenations is a vinylcopper(I) complex. This intermediate can be exploited as a starting point for a variety of trapping reactions. In this manner, an alkyne semihydrogenation can be turned into a dihydrogen-mediated coupling reaction. Therefore, the development of copper-catalyzed (transfer) hydrogenation reactions is closely intertwined with the corresponding reductive trapping reactions. This short review highlights and conceptualizes the results in this area so far, with H2-mediated carbon–carbon and carbon–heteroatom bond-forming reactions emerging under both a transfer hydrogenation setting as well as with the direct use of H2. In all cases, highly selective catalysts are required that give rise to atom-economic multicomponent coupling reactions with rapidly rising molecular complexity. The coupling reactions are put into perspective by presenting the corresponding (transfer) hydrogenation processes first.1 Introduction: H2-Mediated C–C Bond-Forming Reactions2 Accessing Copper(I) Hydride Complexes as Key Reagents for Coupling Reactions; Requirements for Successful Trapping Reactions 3 Homogeneous Copper-Catalyzed Transfer Hydrogenations4 Trapping of Reactive Intermediates of Alkyne Transfer Semihydrogenation Reactions: First Steps Towards Hydrogenative Alkyne Functionalizations 5 Copper(I)-Catalyzed Alkyne Semihydrogenations6 Copper(I)-Catalyzed H2-Mediated Alkyne Functionalizations; Trapping of Reactive Intermediates from Catalytic Hydrogenations6.1 A Detour: Copper(I)-Catalyzed Allylic Reductions, Catalytic Generation of Hydride Nucleophiles from H26.2 Trapping with Allylic Electrophiles: A Copper(I)-Catalyzed Hydroallylation Reaction of Alkynes 6.3 Trapping with Aryl Iodides7 Conclusion
Keywords: cross-coupling; dihydrogen; copper; catalysis; alkynes